Pobreza urbana : as condições de habitação popular no município de Passo Fundo/RS - Santos, Ana Cláudia Ribeiro dos (2011)
The present dissertation approaches the urban poverty identified through the popular housing in the city of Passo Fundo. To this end, it was sought, initially, to reflect on the meanings of urban poverty, which according to documentary and bibliographical research has shown that it has intensified in the same proportion as the increase of urbanization. The discussion of the contemporary view showed that although it is a category widely debated by scholars from various areas of knowledge, the conceptions produced are marked by the breadth of the subject. By means of a historical review of the socioeconomic conditions of Passo Fundo, it was discussed some historical features that permeate elements from its colonization to the present day. The economic structure of the city was approached in order to understand its dynamic economy. It was later drawn an overview of popular neighborhoods, whose reflection showed that the city brings together, legally, 22 demographic sectors/neighborhoods and about ninety neighborhoods and settlements are considered irregular. Soon after it was discussed the public policy on housing in the city of Passo Fundo. To do so, through brief contextualization and retrospective, it was discussed the policy of housing in Brazil, with emphasis on its legal frameworks. Then, with elements subsidized by IBGE on substandard clusters it was established a panorama of the housing conditions in the city, with reference to the period of 2010. One of the remarks of the final consideration is that there is a pressing need to establish an urban policy, in Passo Fundo, which promotes the social-spatial integration of the poor, as a means of echoing the legitimate conception of law backed by the Universal Declaration of Human Rights, 1948.